2021
DOI: 10.1016/j.compbiomed.2021.104613
|View full text |Cite
|
Sign up to set email alerts
|

In silico investigation on the inhibitory effect of fungal secondary metabolites on RNA dependent RNA polymerase of SARS-CoV-II: A docking and molecular dynamic simulation study

Abstract: The newly emerged Coronavirus Disease 2019 (COVID-19) rapidly outspread worldwide and now is one of the biggest infectious pandemics in human society. In this study, the inhibitory potential of 99 secondary metabolites obtained from endophytic fungi was investigated against the new coronavirus RNA-dependent RNA polymerase (RdRp) using computational methods. A sequence of blind and targeted molecular dockings was performed to predict the more potent compounds on the viral enzyme. In the next step, the five sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 36 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…DSSP analysis also revealed no significant changes in various types of secondary structures over the span of simulation time ( Table 4 ). Principal Component Analysis ( PCA ) provides the main components of protein motion during the simulation [ 63 ]. The 2D diagram of the RBD movements for different systems was obtained using the projection of the first two principal components.…”
Section: Resultsmentioning
confidence: 99%
“…DSSP analysis also revealed no significant changes in various types of secondary structures over the span of simulation time ( Table 4 ). Principal Component Analysis ( PCA ) provides the main components of protein motion during the simulation [ 63 ]. The 2D diagram of the RBD movements for different systems was obtained using the projection of the first two principal components.…”
Section: Resultsmentioning
confidence: 99%
“…During COVID-19 pandemic condition, the researcher also worked in the area of SMs from endophytic fungi and predicted their inhibitory effect against single RNA-dependent RNA polymerase of coronavirus using molecular docking and simulation tools. The whole-genome data of the viruses and the plants helped in the prediction of two metabolites (namely dankasterone B and pyrrocidine A), which cause inhibition of viral RdRp (mutation associated in SARS-COV-2 genome) (Ebrahimi et al 2021 ). Applying these high-throughput tools, researchers get access to the structure of the metabolite.…”
Section: Multi-omic Tools In Basidiomycete Metabolite Regulation Studiesmentioning
confidence: 99%
“…The inhibitory potential of various secondary metabolites to New Coronavirus RNA dependent RNA polymerase (RdRp) was studied, and the selected compounds were further evaluated by molecular dynamics (MD) simulation. It was found that 18 methoxy-cytochalasin J (MCJ) and pyrrolidine A are more effective virus inhibitors than other compounds, so they can be used for further experimental research [ 82 ].…”
Section: Reactions Catalyzed By Fmos In Natural Product Biosynthesismentioning
confidence: 99%